2020
DOI: 10.2147/dddt.s258857
|View full text |Cite
|
Sign up to set email alerts
|

<p>Phoenixin 14 Inhibits High-Fat Diet-Induced Non-Alcoholic Fatty Liver Disease in Experimental Mice</p>

Abstract: Introduction: Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases. The development of NAFLD is closely associated with hepatic lipotoxicity, inflammation, and oxidative stress. The new concept of NAFLD treatment is to seek molecular control of lipid metabolism and hepatic redox hemostasis. Phoenixin is a newly identified neuropeptide with pleiotropic effects. This study investigated the effects of phoenixin 14 against high-fat diet (HFD)-induced NAFLD in mice. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…Liver tissues were fixed in 4% paraformaldehyde and then embedded in paraffin. Paraffin sections (5 μm thick) were cut and mounted on glass slides for haematoxylin-eosin (HE) staining as described previously ( Yang F. et al, 2020 ). The histological images were captured with a light microscope (Olympus, Tokyo, Japan) at ×200 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…Liver tissues were fixed in 4% paraformaldehyde and then embedded in paraffin. Paraffin sections (5 μm thick) were cut and mounted on glass slides for haematoxylin-eosin (HE) staining as described previously ( Yang F. et al, 2020 ). The histological images were captured with a light microscope (Olympus, Tokyo, Japan) at ×200 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that in mice with experimentally induced non-alcoholic fatty liver disease, PNX suppressed circulating levels of alanine and aspartate aminotransferases, cholesterol, and triglyceride as well as attenuating lipid deposition in the liver. The same study showed that beneficial effects of PNX administration on HFD-induced liver disease were mediated via attenuation of AMPK/SIRT activation [72].…”
Section: Cell-protective and Anti-inflammatory Effects Of Phoenixinmentioning
confidence: 85%
“…A recently published animal study showed that PNX is able to protect against high-fat diet (HF)-induced non-alcoholic fatty liver disease in mice [72]. It was found that in mice with experimentally induced non-alcoholic fatty liver disease, PNX suppressed circulating levels of alanine and aspartate aminotransferases, cholesterol, and triglyceride as well as attenuating lipid deposition in the liver.…”
Section: Cell-protective and Anti-inflammatory Effects Of Phoenixinmentioning
confidence: 99%
“…Finally, liraglutide has also been shown to increase insulin sensitivity [ 343 , 344 , 345 ]. In addition, Phoenixin 14—a neuropeptide—induced weight loss and liver mass reduction and had an anti-inflammatory role partly due to activation of the AMPK/SIRT1 pathway [ 346 ]. This compound could be used against NAFLD.…”
Section: The Role Of Sirtuins In Metabolic Tissuesmentioning
confidence: 99%